2022
DOI: 10.46281/ijibm.v6i1.1900
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and the Performance of Islamic Banks in Indonesia

Abstract: Covid-19 has an impact on the profitability of Islamic Banks in Indonesia. Islamic banks' profitability in Indonesia tends to decline during a covid-19 outbreak. Although declining, the profitability indicators measured by Return on Asset and Net Operating Margin are more stable than Return on Equity. The average Return on Equity declined sharply in the fourth quarter of 2021. This study aims to analyze the determinants of the profitability of Islamic banks, including internal bank factors and macroeconomic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Within the scope of the big data credit model, banks are better able to identify and manage risks even when making loans to businesses without security or guarantees. Khalifaturofi'ah et al [19] demonstrated that banks with a higher investment in digital transformation provide a higher number of cheaper and faster guaranteed loans. As a result, banks have been able to bring more long-tail customers who lack collateral and credit history into their credit services through the use of digital technology [20].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Within the scope of the big data credit model, banks are better able to identify and manage risks even when making loans to businesses without security or guarantees. Khalifaturofi'ah et al [19] demonstrated that banks with a higher investment in digital transformation provide a higher number of cheaper and faster guaranteed loans. As a result, banks have been able to bring more long-tail customers who lack collateral and credit history into their credit services through the use of digital technology [20].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…al., 2023). Khalifaturofi'ah et. al., (2022) revealed that both internal and macroeconomic factors become a critical prosess when assessing the performance of Islamic banks in Indonesia.…”
Section: Introductionmentioning
confidence: 99%